2008
DOI: 10.1002/jmor.10653
|View full text |Cite
|
Sign up to set email alerts
|

Development of respiratory structures in embryos and first and second instars of the bark scorpion, Centruroides gracilis (Scorpiones: Buthidae)

Abstract: The SEM was used to study the development of respiratory structures in successive stages in relation to the overall changes occurring in the scorpions. Book lung development is a slow process, starting with spiracles and a sac-like atrium in the early embryo and continuing lamellar formation to 150 or more in the adult. In the embryo, the primordial epithelial cells become aligned in a planar pattern as they secrete granules of material that aggregate spontaneously to form the cuticular walls of the lamellae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(65 citation statements)
references
References 63 publications
10
55
0
Order By: Relevance
“…The development of scorpion and spider book lungs is uniform and fi rst becomes apparent as an ectodermal invagination at the posterior margin of an opisthosomal segment (Laurie 1890 ;Purcell 1909 ;Farley 2008 ). This invagination then increases in size, forming a pulmonary sac, while the limb bud itself ingresses into the ectoderm of the segment (Farley 2011 ).…”
Section: Book Gills and Book Lungsmentioning
confidence: 97%
“…The development of scorpion and spider book lungs is uniform and fi rst becomes apparent as an ectodermal invagination at the posterior margin of an opisthosomal segment (Laurie 1890 ;Purcell 1909 ;Farley 2008 ). This invagination then increases in size, forming a pulmonary sac, while the limb bud itself ingresses into the ectoderm of the segment (Farley 2011 ).…”
Section: Book Gills and Book Lungsmentioning
confidence: 97%
“…In more advanced embryos, the first indication of respiratory structures are bilateral spiracles at the posterior margin of developing opisthosomal sternites (Farley, 1999(Farley, , 2001a(Farley, ,b,c, 2005(Farley, , 2008(Farley, , 2011. Those observations are from representative species from basal scorpion families Buthidae, Vaejovidae and Iuridae (Fet et al, 2000;Coddington et al, 2004).…”
Section: Comparison With Scorpion Book Lung Developmentmentioning
confidence: 90%
“…Kjellesvig-Waering (1986) suggested that marginal spiracles in fossil scorpions were openings for passage of water to gills above the posterior edge of abdominal plates or sternites. Many scorpion embryos of diverse taxa were examined with SEM (Farley, 1999(Farley, , 2001a(Farley, ,b,c, 2005(Farley, , 2008(Farley, , 2011, but no indication of such opening or gills was observed.…”
Section: Comparison With Scorpion Book Lung Developmentmentioning
confidence: 99%
See 2 more Smart Citations